2022
DOI: 10.1021/acsami.2c09535
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Atomically Dispersed Pt in a SnO2 Thin Film under Reaction Conditions: Origin of Its High Performance in Micro Electromechanical System Gas Sensor Catalysis

Abstract: A battery-driven micro electromechanical system (MEMS) gas sensor has been developed for household safety when using natural gas. The heart of the MEMS gas sensor is a 7.5 at % Pt−SnO 2 thin film catalyst deposited on the SnO 2 sensor layer. The catalyst enhances the sensitivity to methane, though its structure under working conditions is unclear. In this study, in situ XAFS was applied to a 7.5 at % Pt−SnO 2 catalyst layer deposited on a Si substrate, and we demonstrated that atomically dispersed Pt maintains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Murata et al demonstrated that Pt atoms dispersed randomly in a SnO 2 lattice underwent partial reduction without losing their lattice positions under reducing gases such as 1% CH 4 and 1% H 2 . 117 In situ XAFS measurements showed no formation of Pt nanoparticles even during the reaction ( Fig. 4h ).…”
Section: Application Of Surface Acoustic Wave (Saw) In Gas Detectionmentioning
confidence: 94%
“…Murata et al demonstrated that Pt atoms dispersed randomly in a SnO 2 lattice underwent partial reduction without losing their lattice positions under reducing gases such as 1% CH 4 and 1% H 2 . 117 In situ XAFS measurements showed no formation of Pt nanoparticles even during the reaction ( Fig. 4h ).…”
Section: Application Of Surface Acoustic Wave (Saw) In Gas Detectionmentioning
confidence: 94%
“…In addition, as the temperature increases, the resistance decreases due to the semiconducting nature of SnO 2 . However, as the temperature is increased to around 160 °C, a small increase in resistance is observed, which is a consequence of the conversion of molecular oxygen (O 2 − ) into atomic oxygen (2O − ) and thus the trapping of more free electrons [ 153 , 154 , 155 , 156 ]. The interaction with the adsorbed oxygen (O − ) by the SO 2 gas molecules on the surface of SnO 2 releases the trapped charge carriers back.…”
Section: Sensing Of Co Ch 4 No No 2 ...mentioning
confidence: 99%
“…Thin films are widely used for various applications, including micro-electromechanical systems, sensors, desalination, filtration, air filters, and integrated circuits . They can be coated on substrates or used as free-standing materials depending on the application.…”
Section: Introductionmentioning
confidence: 99%